Human foot muscle strength and its association with sprint acceleration, cutting and jumping performance, and kinetics in high-level athletes - Tourillon, R.; Michel, A.; Fourchet, F.; Edouard, P.; Morin, J. B. (Journal of Sports Sciences, 2024)
The primary objective of this study was to investigate the relationship between metatarsophalangeal joint (MTPj) flexion torque and sprint acceleration, cutting and jumping performance, and kinetics. A secondary aim was to explore this relationship when MTP flexion strength was associated with other foot and lower limb neuromuscular outputs. After an initial MTPj flexion torque assessment using a custom-built dynamometer, 52 high-level athletes performed the following tasks on a force platform system: maximal sprint acceleration, 90-degree cutting, vertical and horizontal jumps, and foot-ankle hops. Their foot posture, foot passive stiffness and foot-ankle reactive strength were assessed using the Foot Posture Index, the Arch Height Index Measurement System and the Foot-Ankle Rebound Jump Test. Ankle plantarflexion and knee extension isometric torque were assessed using an isokinetic dynamometer. During maximal speed sprinting, multiple linear regressions suggested a major contribution of MTPj flexion torque, foot passive stiffness and foot-ankle reactive strength to explain 28% and 35% of the total variance in the effective vertical impulse and contact time. Ankle plantarflexor and quadriceps isometric torques were aggregately contributors of acceleration performance and separate contributors of cutting and jumping performance. In conclusion, MTPj flexion torque was more strongly associated with sprinting performance kinetics especially at high-speed.